Motor competence moderates relationship between moderate to vigorous physical activity and resting EEG in children with ADHD. (October 2019) - Yu, Chien-Lin; Chueh, Ting-Yu; Hsieh, Shu-Shih; Tsai, Yu-Jung; Hung, Chiao-Ling; Huang, Chung-Ju; Wu, Chien-Ting; Hung, Tsung-Min
Abstract: Background: Children with ADHD display abnormal electroencephalographic (EEG) activity, in particular an elevated theta to beta ratio (TBR) during the resting state. Aims: To assess whether the motor competence (MC) and moderate–to-vigorous physical activity (MVPA) were associated with TBR, and whether MC moderated the relationship between MVPA and TBR. Methods: Data from a total of 73 children with ADHD (69 boys and 4 girls, mean age = 9.92 years, SD = 1.56 years) were analyzed. EEG readings were taken as participants rested with their eyes open. MC was assessed using the Movement ABC-2 measure, and MVPA was evaluated using an ActiGraph accelerometer. Results: MC was negatively associated with TBR, and an interaction between MVPA and MC on TBR was observed. It was found that there was a negative correlation between MVPA and TBR in those with high MC, whereas the relationship was positive in those with low MC. Conclusions and implications: The current study found that increased MC was associated with less deviant cortical activity in the resting state, as measured by TBR, and that MC moderated the relationship between MVPA and TBR after controlling for age. It highlights the importance of increasing motor competence within physical activity to improve cortical functioning of children with ADHD. Highlights: Better motor competence (MC) was associated lower theta to beta ratio (TBR) in children with ADHD. MC moderates the relationship between moderate to vigorous physical activity (MVPA) and TBR. Physical activity contain motor ingredient is important for normalizing cortical functioning in children with ADHD.